Antiaging function of Chinese pond turtle (Chinemys reevesii) peptide through activation of the Nrf2/Keap1 signaling pathway and its structure-activity relationship - Wang, Qianqian; Yang, Zherui; Zhuang, Jiachen; Zhang, Junhui; Shen, Fei; Yu, Peng; Zhong, Hao; Feng, Fengqin (Frontiers in Nutrition, 2022)
Chinese pond turtle is a traditional nourishing food with high nutritional value and bioactivity, and has been considered as a dietary remedy for prolonging the lifespan since ancient times. However, only limited information about their effects on longevity is available. The study was performed to assess the antioxidative activities and anti-aging potential of Chinese pond turtle peptides (CPTP) using Drosophila melanogaster model and uncover the possible mechanisms underlying the beneficial effects. CPTP exhibited excellent antioxidative capability in vitro, with IC50 values of 3.31, 1.93, and 9.52 mg/mL for DPPH, ABTS, and hydroxyl radical scavenging, respectively. In vivo, 0.8% of CPTP significantly extended the mean and median lifespan of female Drosophila by 7.66% and 7.85%, followed with the enhanced resistance to oxidative and heat stress. Besides, CPTP remarkably increased the antioxidant enzyme activities, and diminished the peroxide products accumulation. Furthermore, CPTP upregulated the relative mRNA expression of antioxidant-related genes, including nuclear factor-erythroid-2-like 2 (Nrf2) and its downstream target genes, while downregulated the expression of kelch-like ECH-associated protein 1 (Keap1). Taken together, CPTP displayed promising potential in both antioxidant and anti-aging effects on Drosophila by targeting the Nrf2/Keap1 pathway. Further peptide sequence determination revealed that 89.23% of peptides from the identified sequences in CPTP could exert potential inhibitory effects on Keap1. Among these peptides, ten representative peptide sequences could actively interact with the binding sites of Keap1-Nrf2 interaction through hydrogen bonds, van der Walls, hydrophobic interactions, and electrostatic interactions. Conclusively, CPTP could be utilized as health-promoting bioactive peptides with antioxidant and anti-aging capacities.